Subregional efforts to improve childhood cancer care in the Andean countries - Maria del Carmen Calle; Marisela Mallqui; Luis Beingolea; Forlly Chavez; Patricia Gallardo; iliana Vásquez; Hernan Sepúlveda (Pan American Health Organization, 2023)
Cancer is one of the leading causes of death in children and adolescents younger than 19 years. An estimated 10 000 deaths are caused by this disease annually in this age group in Latin America and the Caribbean. In high-income countries, the survival of children and adolescents with neoplasms can reach 85%; however, in middle- and low-income countries, despite progress, survival rates are significantly lower (between 10% and 60%). Important inequities exist is survival from childhood cancer that need to be addressed through decisive actions from the health systems. This report describes the work of the ministries of health and the Secretariat of the Andean Health Organization (Organismo Andino de Salud - Convenio Hipólito Unánue (ORAS-CONHU)), to develop the Andean Cancer Prevention and Control Policy, with consideration given to childhood cancers. The policy was based on analysis of the cancer situation in the six Andean countries - Bolivia (Plurinational State of), Colombia, Chile, Ecuador, Peru and Venezuela (Bolivarian Republic of) - between 2015 and 2020, and it was approved in 2022. An in-depth study is currently being carried out on the situation of childhood cancer in the Andean countries.